Pengaruh Mata Kuliah Pengukuran Besaran Listrik (PBL) Teori Terhadap Hasil Praktikum Pengukuran Besaran Listrik (PBL) Ditinjau dari Motivasi Belajar Mahasiswa IT - PLN - Dwi Anggaini (Energi & Kelistrikan, 2020)
Electrical Measurement is one of the courses in Electrical Engineering, which consists of theoretical and practical subjects. The system of taking practical courses should be implemented after taking theoretical courses or simultaneously in one semester. But in reality there are still students who take practical courses before taking theoretical courses, especially in the Electrical Measurement course. Based on the description above, the researcher would describe whether there is an influence of learning outcomes of Electrical Measurement Theoretical Courses on learning outcomes of Electrical Measurement Practical Courses. This research must be held to measure motivation to learn of students and learn the interaction between learning motivation and Electrical Measurement Practical Courses. This research was analyzed using two-way ANAVA (Two Way ANOVAI) with a 2x2 factorial design and further tests using Tukey Test. The result was there is an interaction between Electrical Measurement Theoretical Courses and student's learning motivation of their Electrical Measurement Practical Courses' results. This can be seen from 16.66 and Ft = 4.04 at α = 0.05 with Fh> Ft means H1 is accepted.